Dikes on permafrost foundations in northern Manitoba - Macpherson, J. G.; Watson, G. H.; Koropatnick, A. (Canadian Geotechnical Journal, 1970)
The development of hydro-electric power within the areas of low relief of northern Canada often requires long dikes to impound a reservoir. Much of this region lies within a zone of discontinuous permafrost, and dike design must allow for foundations varying from soft alluvial materials which will settle during or shortly after construction, to frozen strata with a high ice content which will settle as the ice thaws due to heat loss from the reservoir.This paper describes the approach to design and construction of dikes for the Kettle Generating Station in northern Manitoba, and includes a description of the instrumentation installed in an attempt to correlate the relationship between the rate of thawing of the permafrost and the rate of drainage of free water from the foundation.